(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Blockchain technology has emerged as a transformative force, disrupting traditional industries by providing secure, transparent, and decentralized solutions. In recent years, its application in the healthcare sector has gained momentum, offering innovative solutions to address challenges in data security, interoperability, and trust. This paper explores the latest developments in blockchain technology and its promising applications in healthcare learning systems. The evolution of blockchain technology has seen the introduction of advanced consensus algorithms, smart contracts, and decentralized storage mechanisms. These features contribute to enhanced security, immutability, and transparency of data, making blockchain an ideal candidate for addressing the complex and sensitive nature of healthcare data. In the context of healthcare learning systems, blockchain facilitates the creation of secure and interoperable platforms for storing and exchanging educational content, certifications, and training records.